Development of Universal Wheelchair Transporter - F.A Zulkepli., N.; Khusairi, S.; S.B Shaari, M.; S Khusaini, N.; N Aziz., N.; I Sainan, K.; Mohamed, Z. (International Journal of Engineering and Technology, 2018)
This work introduces a new universal wheelchair transporter to transport a conventional wheelchair from one point to another. The chosen design concept had been selected using Pugh chart selection method [13], considering all aspect contributed that give the highest weightage. The 3D design utilized CATIA software to visualize the product. Mecanum wheels were chosen to move the platform due to its flexibility and maneuverability in any direction without turning the universal transporter. The objective of this project is to develop a fully functional universal wheelchair transporter to transport a patient from one room to another room in the hospital. The performance of the product design is then tested using Finite Element Analysis and shows good results.Â Â